2000
DOI: 10.4049/jimmunol.164.4.2053
|View full text |Cite
|
Sign up to set email alerts
|

Ras, Protein Kinase Cζ, and IκB Kinases 1 and 2 Are Downstream Effectors of CD44 During the Activation of NF-κB by Hyaluronic Acid Fragments in T-24 Carcinoma Cells

Abstract: We have investigated the ability of hyaluronic acid (HA) fragments to activate the transcription factor NF-κB. HA fragments activated NF-κB in the cell lines T-24, HeLa, MCF7, and J774. Further studies in T-24 cells demonstrated that HA fragments also induced IκBα phosphorylation and degradation, κB-linked reporter gene expression, and ICAM-1 promoter activity in an NF-κB-dependent manner. The effect of HA was size dependent as neither disaccharide nor native HA were active. CD44, the principal cellular recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 59 publications
(54 reference statements)
5
65
0
Order By: Relevance
“…It has also been reported that gene expression of MMP-1, MMP-3, and MMP-9 is regulated by the activation of protein kinase C in chondrocytes (38,39). Protein kinase C was shown to be a downstream effector of CD44 during the activation of NF-B by HA fragments in T-24 carcinoma cells (40). Thus, HA 6 treatment seems to disturb the stabilization of cytoskeletal conformation accomplished by high molecular mass HA-CD44 interactions, consequently leading to the activation of transcription factors affecting catabolism.…”
Section: Discussionmentioning
confidence: 94%
“…It has also been reported that gene expression of MMP-1, MMP-3, and MMP-9 is regulated by the activation of protein kinase C in chondrocytes (38,39). Protein kinase C was shown to be a downstream effector of CD44 during the activation of NF-B by HA fragments in T-24 carcinoma cells (40). Thus, HA 6 treatment seems to disturb the stabilization of cytoskeletal conformation accomplished by high molecular mass HA-CD44 interactions, consequently leading to the activation of transcription factors affecting catabolism.…”
Section: Discussionmentioning
confidence: 94%
“…Following functional validation of this tet-regulated CD44 expression system, RNA was extracted from HA-stimulated MCF7F-B5 cells in the absence and presence of CD44 expression and the transcriptional targets of HA/CD44 signaling determined by microarray analysis. Prior studies have indicated that the fragment size of HA impacts on the signaling competency of CD44 (McKee et al, 1996;Fitzgerald et al, 2000). Accordingly, RNA samples were harvested from cells stimulated with HA of an approximate molecular weight of 220 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the observation that HA 6 and not HA 4 have the potential to activate MMP-13 transcription is consistent with our hypothesis that the cell signaling in chondrocytes is initiated by the displacement of HMW-HA, resulting in the declustering of CD44 in the cell membrane and destabilization of the cortical cytoskeletal conformation. Cytoskeletal rearrangements are known to be involved in the induction of MMPs (65,66) and include activation of protein kinase C and NFB (67).…”
Section: Discussionmentioning
confidence: 99%